Principles of adult learning theory and implications for learning and teaching - Umarova Malika Kiyamiddinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
English is an international language used for communication in education, technology, commerce, and politics, so it is studied as a foreign language in many countries around the world. The article is mainly devoted to the study of a new phenomenon - teaching English as a foreign language to adults using CLT. The purpose of this study was to find new ways to improve communicative competence.